Organoleptic Test of the Quality of Sweet Soy Sauce Made from Turi Seeds - I Ketut Gede Adi Surita; I Gede Adi Sistha Winata (PT FORMOSA CENDEKIA GLOBAL, 2025)
Sweet soy sauce is one of the favorite soy-based food complements for the majority of Indonesians, which extends to the interior. In general, sweet soy sauce is made from selected soybeans processed by fermentation. In fact, Indonesia is rich in various types of grains other than soybeans that can be used as an alternative to making sweet soy sauce. Many Indonesians still do not know the alternative ingredients for making sweet soy sauce. To overcome this problem, it is necessary to have an alternative in making sweet soy sauce with high nutritional value or at least have the same quality as soybeans. Seeds from the turi plant can be used as an alternative raw material in making sweet soy sauce because turi seeds have a nutritional content composition that is not much different from soybeans and the utilization of turi seeds in Indonesia has not been maximized. The methods used to obtain the data and information needed in this study are experimental tests, documentation, and organoleptic tests supported by components such as questionnaires, panelist tests, and Likert scales. This study used fairly trained panelists. The results obtained from the organoleptic test, namely in terms of taste, texture, aroma, and color, have very good interpretation criteria.